Ovarian fibrothecoma—Causing menstrual disorder and hirsutism: Case report and review of literature - Sunday Isaac Omisakin; Aloy Okechukwu Ugwu; Luqman Adedotun Adebayo; Kabir Bolarinwa Badmus (International Journal of Medicine and Health Development, 2021)
Fibrothecomas are solid tumors of the ovary. They have been described as rare ovarian neoplasms with varied clinical manifestations. It is an uncommon tumor that originates from stromal cells accounting for 3–4% of all ovarian tumors. We present a case of a 23-year-old nulliparous undergraduate who presented to our outpatient department with secondary amenorrhea, hirsutism, and acne of one-year duration. Her symptoms worsened overtime that necessitated her presentation. Clinical examination revealed signs of hyperandrogenism with a 16-week-sized abdominopelvic mass. She had surgical excision of the mass after work-up. Her menses returned and other signs of hyperandrogenism resolved. Histopathology confirmed fibrothecoma.